ISSUES AND TRENDS WAQF HOUSING IN PENANG MALAYSIA - Baihaki Abdullah; Azreen Hamiza Abdul Aziz (Journal of Islamic, Social, Economics and Development, 2023)
In Malaysia, the development of waqf housing aims to address Malaysian Muslims' housing issues, which are eroding property ownership in the city. However, policymakers in Malaysia have made efforts to understand and manage housing crisis. Furthermore, a major housing concern is that low-income people frequently struggle to find affordable and comfortable housing. The goal of this paper is to look into the various issues and trends that waqf housing faces in Malaysia. The research design of basic qualitative is used secondary data (thesis and journal articles related to the science social study) with as data collection method. Data is analysed using basic qualitative approach. This article introduces housing crisis in Malaysia, the concept waqf housing, issues and trends waqf housing in Penang Malaysia , and the future direction is recommended.